2022
DOI: 10.1017/s0959270922000193
|View full text |Cite
|
Sign up to set email alerts
|

Range-wide changes in the North American Tufted Puffin Fratercula cirrhata breeding population over 115 years

Abstract: Summary Regional and local studies suggest that the Tufted Puffin Fratercula cirrhata in North America is declining in portions of its range. However, whether the overall population is declining, or its range is contracting with little change to the overall population size, is unknown. To examine population trends throughout its North American range, we assembled 11 datasets that spanned 115 years (1905–2019) and included at-sea density and encounter estimates and at-colony burrow and bird counts. We assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This is the first information on movements of tufted puffins across the year (see Schaefer et al 2022 for non-breeding movements), currently a candidate species for listing under the US Endangered Species Act. Populations of puffins have declined in several locations due, in part, to fisheries-associated net mortality, oil pollution, increased predation, harvest, and environmental change (Piatt & Kitaysky 2020, Pearson et al 2023), and the Japanese population is predicted to be extirpated in the near future (Brazil 2018). Our 3-dimensional approach al lowed us to gain insight into potential mechanisms driving population declines, and these results have broad implications for the conservation of other sympatric species.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first information on movements of tufted puffins across the year (see Schaefer et al 2022 for non-breeding movements), currently a candidate species for listing under the US Endangered Species Act. Populations of puffins have declined in several locations due, in part, to fisheries-associated net mortality, oil pollution, increased predation, harvest, and environmental change (Piatt & Kitaysky 2020, Pearson et al 2023), and the Japanese population is predicted to be extirpated in the near future (Brazil 2018). Our 3-dimensional approach al lowed us to gain insight into potential mechanisms driving population declines, and these results have broad implications for the conservation of other sympatric species.…”
Section: Discussionmentioning
confidence: 99%
“…Tufted Puffins are a long-lived seabird species in the family Alcidae, with a broad distribution in the temperate North Pacific Ocean (Piatt and Kitaysky 2020; Figure 1). Although populations of Tufted Puffins appear to be stable in some parts of their distribution, they have exhibited massive declines during the past 30 years in the northern Gulf of Alaska and at most colonies on the U.S. West Coast and British Columbia (except Triangle Island; Gaston et al 2009, Blight and McClelland 2022, Stephensen 2022, Pearson et al 2023). They are currently listed as special concerns in California, as sensitive in Oregon, as endangered in Washington, and as imperiled in British Columbia (Hanson et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this species has been in decline in Japan since the 1970s (Senzaki et al 2020). It has been suggested that population declines have occurred in response to rising ocean temperatures, which are thought to have shifted forage fish composition and distribution in the region (Jones et al 2019, Pearson et al 2023). Assessing population genetic structure and gene flow will help to improve our knowledge about this species and provide further insights into how best to conserve populations across their range.…”
Section: Introductionmentioning
confidence: 99%